PENGARUH PENERAPAN METODE STRUKTURAL ANALITIK SINTETIK (SAS) DENGAN BERBANTUAN MEDIA POWERPOINT TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS II SEKOLAH DASAR - Salsabilla, Maghfira; Nurmahanani, Indah; Sholihah Rosmana, Primanita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is backgrounded by the leak of second grade students of an elementary school to beginning reading skills. This research has a purpose to find out the effect of the Structural Analytic Synthetic (SAS) method assisted with powerpoint media to students beginning reading skills on second grade students of an elementary school in Purwakarta Regency. The research used was pre-experiment research with one-group pretest-posttest design. Data collection techniques in this research used tests (pretest and posttest) and non-tests (observation). The sample of this research was 23 students on second grade class of an elementary school in Purwakarta Regency. Descriptive statistical data analysis was carried out on pretest and posttest total score data. After treatment, it was found that there was an increase in the average score, the increase in the average score was large enough, from 72.39 to 82.17. Furthermore, a t-test (paired samples test) was carried out on the total pretest and posttest scores. It can be seen that there is an effect of implementing Structural Analytic Synthetic (SAS) method assisted with powerpoint media to students beginning reading skills as seen from the significant value of <0.001 which is less than 0.05, then there is an effect of iplementing structural analytic synthetic (SAS) method assisted with powerpoint media to students beginning reading skills. Therefore, it can be concluded that the structural analytic synthetic (SAS) method assisted with powerpoint media there is an effect to students beginning reading skills.   Keywords: beginning reading skills, powerpoint media, Structural Analytic Synthetic (SAS) method